“High Tech And Low Tech” Industries as Moderating The Value Relevance of Accounting Information Research and Development (R&D) Costs - Arifany Ferida; Mohammad Alfian; Muchammad Sofyan Firmansyah (JPA : Journal of Public Accounting, 2021)
Accounting information contained in financial statements must be able to influence the decision making of users (investors). The concept of value relevance of financial statements developed by Ohlson (1995) emerged, namely how big the role of accounting information in influencing investor decision making which in turn affects stock prices. Information on the R&D costs of companies belonging to high tech industries may be priced higher than companies belonging to low tech industries. So it is expected that the relevance of information on the R&D costs of companies belonging to high tech industries is higher than companies belonging to low tech industries. This study aims to examine the value relevance of research and development (R&D) cost accounting information and to examine the value relevance of research and development (R&D) accounting information for companies belonging to high tech industries, which are higher than companies belonging to low tech industries. The population in this study were all companies listed on the Indonesia Stock Exchange in 2015-2017. The sampling technique used purposive sampling with company criteria that revealed research and development (R&D) costs in 2015-2017. The number of companies that meet the sample criteria are 47. Data analysis in this study uses Partial Least Square (PLS) with Warp PLS 6.0 application. The results of this study prove that research and development (R&D) accounting information has a positive and significant effect on firm value. However, the results of the study failed to prove that the value relevance of research and development (R&D) accounting information for companies included in high tech industries was higher than companies included in low tech industries.